Enhancing Students’ English Engagement and Competence Through Educative Games - Aryawira Pratama; Retno Wulan; Melli Kusmaningrum; Masita Arianie; Khoirunnisa (STAIN Sultan Abdurrahman Kepulauan Riau, 2026)
Educational game-based learning has become increasingly prevalent in global educational contexts, extending beyond traditional English classrooms and contributing to increased student motivation, engagement, and competence. This study examined the effectiveness of integrating educational games into English language learning compared with conventional teaching methods in a junior high school in Jambi Province, Indonesia. English instruction at the junior high school level often faces challenges, particularly because many students enter secondary education with limited prior exposure to English. To address this issue, the present study investigated the use of several educational game applications—Duolingo, Quizlet, ABCmouse, and Kahoot—to improve English language skills among seventh-grade students over one semester. The research employed a quantitative experimental design involving 58 students divided into two groups: an experimental group (n = 29) that used educational games and a control group (n = 29) that received conventional instruction. Data were collected through pre-tests and post-tests assessing vocabulary, grammar, and communicative competence. Statistical analysis using an independent samples t-test revealed no significant difference between groups at the pre-test stage (t = 0.45, p = 0.65). However, after the intervention, the experimental group demonstrated significantly higher post-test scores (M = 73, SD = 4) than the control group (M = 65, SD = 6), with a significant difference (t = ?6.334, p < 0.001) and a large effect size (d = 1.63). These findings indicate that integrating educational games can substantially enhance students’ engagement and English language proficiency. Practically, this study highlights the potential of combining multiple educational game applications to support technology-integrated English instruction and improve learning outcomes in Indonesian secondary schools.